Chest Reconstruction in Thoracic Dystrophy. Issue 250 (December 1971) - Barnes, N. D.; Hull, D.; Milner, A. D.; Waterston, D. J.
Abstract : Enlargement of the thoracic cage by splitting of the sternum and fixation with bone grafts proved a life-saving measure in a child with thoracic dystrophy and severe respiratory failure whose condition was deteriorating in spite of artificial ventilation. Supported ventilation has, however, remained necessary chiefly because of difficulty in achieving adequate stability of the thoracic cage.